The Effect of an Enriched Sport Program on Children’s Executive Functions: The ESA Program - Gentile, Ambra; Boca, Stefano; Şahin, Fatma Neşe; Güler, Özkan; Pajaujiene, Simona; Indriuniene, Vinga; Demetriou, Yolanda; Sturm, David; Gómez-López, Manuel; Bianco, Antonino; Alesi, Marianna (Frontiers in Psychology, 2020)
Purpose The effects of physical exercise on executive functions (EFs) are well-documented. EFs are involved in daily activities, and their development determines the quality of people’s future life, both in terms of mental health and quality of life. The purpose of the current paper is to evaluate the effects of a physical education program, elaborated within the Enriched Sports Activity Program (ESA Program), an Erasmus + Project, on EFs, namely, visuospatial working memory, inhibitory control, cognitive flexibility, and task switching. Method Data were collected on November 2017 (t1) and May 2018 (t2). At t1, a sample of 357 children from four European countries (Italy, Germany, Lithuania, and Turkey) performed a cognitive test battery made up of Digit Span Forward/Backward, Stroop Task, and Trail Making Test (TMT), whose order was randomized. From November until May, classrooms from the experimental group followed the ESA Program, while classrooms from the control continued with the ordinary physical education class. At t2, children from both experimental and control groups performed again the cognitive battery. Result The repeated measures ANOVA showed a significant effect of the ESA Program on the TMT B and on Digit Span Backward, but no significant effects were found on Digit Span Forward and Stroop Task. Conclusion The introduction of a sport program enriched with cognitive stimuli has beneficial effects for children working memory and cognitive flexibility.